Marital and fertility decision-making: The lived experiences of adolescents and young married couples in Andhra Pradesh and Telangana, India - Crivello, G; Roest, J; Vennam, U; Singh, R; Winter, F (Young Lives, 2018)
This report presents findings from a qualitative sub-study exploring adolescent girls and young couples’ experiences of marital and fertility decision-making in two southern Indian states (Andhra Pradesh and Telangana). Andhra Pradesh and Telangana are among the top states reporting high adolescent fertility: 12 and 11 per cent of young women age 15-19 in Andhra Pradesh and Telangana, respectively, were already mothers or pregnant when surveyed in 2015/16. This research was carried out as part of Young Lives, a longitudinal study of childhood poverty that traced the life trajectories of 3,000 children (in two age groups) and their households located in these states, over a 15-year period. By age 18, around 30 per cent of girls in the Young Lives study had married, and 23 per cent of these married girls had also become mothers.